Data on the physical characterization of oil in water emulsions - Zalazar, Aldana Lourdes (2016)
This article contains experimental data and images for the physical characterization of oil in water emulsions. Mentioned data are related to the research article “Effect of stabilizers, oil level and structure on the growth of Zygosaccharomyces bailii and on physical stability of model systems simulating acid sauces” (A.L. Zalazar, M.F. Gliemmo, C.A. Campos, 2016) [1]. Physical characterization of emulsions was performed through the evaluation of Span and Specific Surface Area (SSA) determined by light scattering using a Mastersizer. Furthermore, microscopy images were recorded by confocal scanning laser microscopy (CSLM). The latter are presented to collaborate in the analysis of emulsion microstructure.